(untitled) (Bangladesh Journal of Medical Science, 2015)
Background: Health inequity is becoming an emerging issue all over the world. Improving maternal health is one of the UN Millennium Development goals. Pregnant women inhabiting urban slums are a high risk group with limited access to health facility. Objective: To study the socio economic profile of the mothers and to study the differentials in utilization of maternal health care by the beneficiaries. Study Design: Descriptive, observational cross-sectional field based study in two purposively selected urban slums of district Dehradun. Results: About 70.9% of mothers belonged to social class II and III and 66% of them belonged to nuclear families. Teenage pregnancy was seen in 8.5%. 93.8% of women received complete antenatal care, majority preferring government hospitals. 93.2% of the women received 100 IFA tablets or more but only 63.7% consumed them for 100 days. Majority of the deliveries were institutional and 79.9% were conducted by trained personnel. About 68.5 % received postnatal care. Conclusion: Although usage of ANC service was high, opportunity to deliver important health services was not fully utilized. Policy and programme to improve the quality and care of antenatal mothers, especially for the poor and under privileged are essential to improve maternal health care. Special interventions should be undertaken on priority basis so as to achieve millennium developmental goals in all population groups. Bangladesh Journal of Medical Science Vol.14(3) 2015 p.280-285